Lipemic Serum in a Toddler with New-Onset Diabetes Mellitus Presenting with Diabetic Ketoacidosis - Waseem, Muhammad; Dave-Sharma, Swati; Kin, Lin Lin; Jara, Fernando (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> Significant hyperlipidemia causing lipemic serum in patients with poorly controlled diabetes is under-reported in children. The recognition of the severe hyperlipidemia is important for proper management and to prevent associated morbidities. Severe hyperlipidemia in patients with diabetic ketoacidosis should be considered. Case report In this case we report a 2-year-old girl with new onset type 1 diabetes mellitus, who presented with severe diabetic ketoacidosis and hyperlipidemia. Hyperlipidemia was resolved with hydration and insulin therapy. Conclusion It is important to diagnose hyperlipidemia by checking serum lipid profile for all pediatric patients presenting with hyperglycemic crisis to prevent morbidities.